CSC126 - Fundamentals of Algorithms and Computer Problem Solving / Faculty of Computer And Mathematical Sciences - UiTM, Faculty of Computer And Mathematical Sciences (Universiti Teknologi MARA (UiTM), 2023)
This course is an introduction to problem solving using a computer programming language. It emphasizes on algorithm development and writing computer programs, as well as common good practices in writing programs. Students will be taught to solve problems involving the 5 basic algorithms of summation, average, counting, as well as determining the minimum and maximum values of a set of data. Teaching methods will involve, lectures, tutorials and practical computer lab work. Students will be assessed through written assessments as well as programing assignments. In the end they are expected to develop the ability to analyze simple problems, organize effective algorithmic solutions for the problems and write computer programs to solve them.